Towards a model for online learning satisfaction (MOLS): re-considering non-linear relationships among personal innovativeness and modes of online interaction. (1st September 2020) - Bervell, Brandford; Umar, Irfan Naufal; Kamilin, Muhammad Hafiz
ABSTRACT: Satisfaction with the use of Learning Management Systems (LMSs) to support online learning has been a concern for institutions. However, several factors such as personal innovativeness, student-material interaction, student-student interaction and student-teacher interaction have been suggested as enablers of satisfaction in online learning environments. What is missing in the literature is determining how these enablers intricately relate to each other in order to understand the effect of their non-linear interactions towards satisfaction in online learning. In view of this, questionnaire-based data was collected from 322 respondents selected through random cluster sampling. Statistical analysis was then conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results from the Model for Online Learning Satisfaction (MOLS) revealed that complex non-linear relationships exist among these variables, such that student-teacher interaction determines student-student interaction whereas personal innovativeness influences student-material interaction. Additionally, student-material interaction influences the extent to which student-teacher interactions as well as student-student interactions occur. The study suggested that all these factors are to be considered carefully and planned out, as they are somewhat interrelated in their effectiveness towards satisfaction in online learning.